Cumplimiento nacional y regional del reglamento de mataderos de segunda categoría y de los centros de faenamiento para autoconsumo de la Ley 19.162, Chile - Luengo, Juan; Morales, María; Ramírez, Jessica (Avances en Ciencias Veterinarias, 2007)
A survey was conducted in all regions of the country in order to know the level of the conditions of Infrastructure, Hygienic-Sanitary, Technical and the Animal’s labourer of the Slaughterhouses and Center for Autoconsumption to the regulations of the law 19.162. The presence and percentage of fulfillment of the elements required were evaluated. The results of 95 Slaughterhouses and 45 Center for Autoconsumption show and average of 80,7% and 92,5% fulfillment respectively.